Enhancing Tax Administration to Micro Businesses Through Digital Technology: An Exploratory Study in Dar Es Salaam, Tanzania - William Clifford Gomera; George Oreku; Innocent Shau (European Scientific Journal, ESJ, 2021)
Many studies have shown the importance of Micro Businesses in widening the tax base. However, a practical approach regarding tax administration of micro businesses has so far never been explored. Additionally, information on the manner in which digital technology addresses challenges of tax administration in the Tanzanian context is limited. Therefore, this study explores the potentials of digital technology in enhancing tax administration of micro businesses. Specifically, the study looks at the current tax administration of micro businesses, the challenges thereon, and the existing potentials of technological solutions in enhancing tax administration of micro businesses. The study used mixed method research approach whereby qualitative and quantitative data were collected through interviews and questionnaires respectively. Interviews were conducted to 24 informants from Tanzania Revenue Authority and questionnaires were administered to 137 micro businesses in Dar Es Salaam, Tanzania. Thematic approach was used to analyse qualitative data and descriptive analysis was used for quantitative data. The study finding reveal that the current tax practices to micro businesses do not comply with tax theories of low administration cost, wide tax base, and simple to administer tax procedures. Additionally, micro businesses face multiple levies, informal operations, and complexity of tax systems that make compliance to tax administration difficult. Moreover, this study established that mobile technology is potential for addressing the challenges. The study contributed to the practical aspect of tax administration that can guide policy makers, researchers and tax administrators in tax administration of micro businesses.